Examining the varying standards of education among pre-schools in Singapore: shortcomings of non-compulsory education - Yeo, Jessica (2017)
This research paper aims to examine the varying standards and quality of education that exists between Pre-schools in Singapore. A qualitative research study was adopted, involving 8 different Pre-schools from low, mid and high-tier categories based on cost of school fees. Findings point to striking differences between low and mid/high-tier schools, with emphasis in these 5 areas: Level of academic difficulty, Preparation for Primary 1, Teacher-to-student ratio, Autonomy, and finally, Exposure to non-academic related activities, which are further discussed in the report. Children enter Primary school having different academic abilities and cultural knowledge, largely shaped by their socio-economic background and Pre-school they attend. As a result, the issue of inequality is reinforced and perpetuated at a young age.